Dynamical characteristics of fastening of a cylindrical shell with a hemispherical shell made of graded porous power ceramic-metal under elastic boundary edges - Sobhani, Emad; Safaei, Babak (Elsevier Sci Ltd, 2023)
For the first time, the dynamical assessment of the fastened hemispherical-cylindrical shell structure (FHCSS) made of porous functionally graded ceramic-metal (FGCM) materials under elastic edge conditions is carried out here. In conformity with this, three forms of pores' distributions add the effect of the pores on the power law FGCM materials. Add-on, ten artificial springs, including six transition and four rotational springs at the start and end of the FHCSS, determine the effect of the elastic edge constraints on the system's dynamic. In addition, the influential relationships of the shell elements of the FHCSS are set up by combining the first shear deformation theory and Donnell's simplifications. Additionally, Hamilton's principle sets up the influential motion equations (IMEs) of shell elements of the FHCSS. Then, a mesh-less procedure, named the generalized differential quadrature method, is set up to discretize the IMEs, fastening equations, and edge equations of the shell elements of the FHCSS. Also, the standard eigenvalue is set up to determine the natural frequencies of the FHCSS. Finally, various novel examples are set up and solved to indicate the effect of the material values, pores, elastic boundary constraints, and geometrical appearance values on the responses of the FHCSS.
Keywords: Fastened hemispherical-cylindrical shells; FGM; Porosity; Free vibration; Elastic boundary condition; GDQM